DIFFERENTIATION SYNDROME IN PROMYELOCYTIC LEUKEMIA : CLINICAL PRESENTATION, PATHOGENESIS AND TREATMENT - Gil Cunha de Santis; Eduardo Magalhães Rego (Mediterranean Journal of Hematology and Infectious Diseases)
Differentiation syndrome (DS) represents a life-threatening complication in patients with acute promyelocytic leukemia (APL) undergoing induction therapy with all-trans retinoic acid (ATRA) or arsenic trioxide (ATO). It affects about 20-25% of all patients and there are no definitive diagnostic criteria. Clinically, DS is characterized by weight gain, fever not attributable to infection, respiratory distress, cardiac involvement, hypotension, and/or acute renal failure. At the histological point of view, there is an extensive interstitial and intra-alveolar pulmonary infiltration by maturing myeloid cells, endothelial cell damage, intra-alveolar edema, inter-alveolar hemorrhage, and fibrinous exsudates. DS pathogenesis is not completely understood, but it is believed that an excessive inflammatory response is the main phenomenon involved, which results in increased production of chemokines and expression of adhesion molecules on APL cells. Due to the high morbidity and mortality associated with DS, its recognition and the prompt initiation of the treatment is of utmost importance. Dexamethasone is considered the mainstay of treatment of DS, and the recommended dose is 10 mg twice daily by intravenous route until resolution of DS. In severe cases (respiratory or acute renal failure) it is recommended the discontinuation of ATRA or ATO until recovery.